Necromancers, buffoons, conspirators: The uses of utopia in Držić's Dubrovnik and Shakespeare's England - Ciglar-Žanić, Janja (1995)
The paper will focus on two (seemingly quite distant) instances of the use of utopian topos by two Renaissance playwrights: William Shakespeare in his romance The Tempest (1610) and the Croatian playwright Marin Držić in his best-known play, the comedy Uncle Maroje (1551). The examination will attempt to show how both the choice of utopian motives for these plays as well as the remarkable parallels in the con/textual functioning of utopia within the entire semantic framework of each play relate to a set of common aesthetic and politico-ideological concerns of the two playwrights. By analysing the specific textual strategies linked to the employment of utopian motives in the two plays, the author will try to demonstrate how the utopian topos was employed by both playwrights precisely for its potential within Renaissance culture to be made into a potent instrument for raising the debate concerning the nature of origins of political power, as issue in many ways central to both Držić and Shakespeare.
Projekt MZOS
ENG